Governmental student funding systems for higher education: an international perspective - Sumei Van Antwerpen; Riaan Dirkse Van Schalkwyk (The Journal of Quality in Education, 2024)
The worldwide surge in demand for higher education (HE) aligns with an increasing need for effective student funding systems, particularly in countries where poverty poses a significant barrier to accessing HE. An international perspective on governmental student funding systems allows us to examine how other governments have implemented these systems to benefit their citizens. The aim of this article is thus to provide a global view of the functioning and challenges pertaining to student funding systems and to shed light on the policies in place in the international landscape. The realist systematic literature review methodology was deemed the most suitable for this study as various scholars have previously studied different facets of the topic. This study aligns with the interpretive research paradigm and qualitative methods. The desired information therefore already exists within the body of knowledge, although it has not yet been analyzed through this particular method. It is evident that both developing and developed countries experience challenges regarding student funding, both in the purpose thereof as well as in the implementation. This is a universal issue, and an in-depth literature review confirmed this phenomenon.